Identification and Classification of Money Laundering Red Flags in the Internal Audit Process: A Role- and Conflict-Based Approach - Akrami, Kimia; Nakhaei, Habibollah; Lari Dashtbayaz, Mahmoud (Business, Marketing, and Finance Open, 2026)
The present study aims to identify common red flags in internal auditing and to examine the impact of the internal auditor’s role and conflicts of interest on the accuracy of their detection. This research was conducted using a qualitative method through interviews with internal auditors and audit committee members of companies listed on the Tehran Stock Exchange and regional exchanges. The findings revealed that red flags include suspicious financial transactions, documentary inconsistencies, unusual employee behaviors, and organizational conflicts. Furthermore, the internal auditor’s role and independence directly increase their sensitivity to red flags, while internal conflicts of interest can reduce detection accuracy and, in some cases, lead to self-censorship or downplaying risks. The study also demonstrated that auditors’ coping strategies consist of negotiation, internalization, and avoidance, with issue severity and organizational support influencing the choice of strategy. The results highlight the importance of auditor independence, continuous training, and conflict of interest management, and recommend that organizations improve red flag detection accuracy through transparent policies and enhanced internal processes.